Diffractive W and Z production at the Fermilab Tevatron - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Albrow, MG; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; et al. (2010)
We report on a measurement of the fraction of events with a W or Z boson which are produced diffractively in p̄p collisions at √s=1.96TeV, using data from 0.6fb⊃-1 of integrated luminosity collected with the CDFII detector equipped with a Roman-pot spectrometer that detects the p̄ from p̄+p→p̄+[X+W/Z]. We find that (1.00±0.11)% of Ws and (0.88±0.22)% of Zs are produced diffractively in a region of antiproton or proton fractional momentum loss ξ of 0.03<ξ<0.10 and 4-momentum transferred squared t of -1